IMPLEMENTATION OF QARDH ON ISLAMIC BANKING INDONESIA BASED ON ISLAMIC ECONOMICS THEORY - Falikhatun -; Sri Iswati; Mohammad Saleh (Conference In Business, Accounting, And Management (CBAM), 2015)
This study aimed to analyze about Qardh implementation on Islamic Banking Indonesia based on Islamic Econonomics Theory. The method of this research is qualitative and the paradigm used interpretative. Data collection are in-depth interviews, observation, and documentation, while the analysis taken is Interpretative Phenomenological Analysis (IPA) and Syar'i Analysis. Interpretative Phenomenological Analysis (IPA) results show that according to the experience of Muqridh implementations object of Qardh on Islamic Banking Indonesia include Salary Down Payment, Hajj Bailout Fund, Gold Rahn, and Hawalah, while the results based on Syar'i Analysis concluded that most of Qardh objects are not in accordance with Islaimc Economic Theory, The proposed ideas is for developing Qardh object, that refers to a social object that has a high Maslahah value for Muslim society in Indonesia, with contract which does not violate Sharâ€™i, such as replace Salary Down Payment into Murabaha financing, Hajj Bailout Funds become Hajj Savings, Gold Rahn becomes Rahn Tasjily, and Hawalah bil Mudaraba / Hawalah bil Musharaka become Syirkah Amlak and Musharaka Mutanaqishah. Â Key Words: Islamic Economic Theory, Interpretative Phenomenological Analysis, Muqridh